2003
DOI: 10.1016/j.ehj.2003.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular structure and diastolic function with human ageing Relation to habitual exercise and arterial stiffness

Abstract: We conclude that in contrast to its ability to favourably modulate the stiffness of large elastic arteries, regular aerobic-endurance exercise does not consistently modulate the changes in LV structure and diastolic function that occur with physiological ageing in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
105
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 42 publications
6
105
2
1
Order By: Relevance
“…29 Given this, it is reasonable to hypothesize that both age and cardiorespiratory fitness are associated with increased LV wall thickness and mass. Gates et al 30 reported that the highest mean values for these LV characteristics were observed in older endurance-trained men, suggesting an additive effect of ageing and exercise behaviour. In contrast to the previous findings, our results indicated that RWT in old, less fit women was significantly thicker than in fit peers.…”
Section: Arterial Stiffnessmentioning
confidence: 97%
“…29 Given this, it is reasonable to hypothesize that both age and cardiorespiratory fitness are associated with increased LV wall thickness and mass. Gates et al 30 reported that the highest mean values for these LV characteristics were observed in older endurance-trained men, suggesting an additive effect of ageing and exercise behaviour. In contrast to the previous findings, our results indicated that RWT in old, less fit women was significantly thicker than in fit peers.…”
Section: Arterial Stiffnessmentioning
confidence: 97%
“…Aortic PWV increases with age, but the difference in aortic PWV between younger and older adults has been shown to be smaller in endurance-trained men, compared with recreationally inactive and sedentary men. 15) One study showed no age-related increase in aortic stiffness in physically active women. 14) Endurance-trained athletes also had greater arterial compliance compared with age-matched sedentary control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Habitual aerobic-endurance exercise attenuates age-associated increases in arterial stiffness in healthy subjects. Aortic PWV increases with age, but the difference in aortic PWV between younger and older adults has been shown to be smaller in endurance-trained men, compared with recreationally inactive and sedentary men.…”
Section: Discussionmentioning
confidence: 99%
“…Gates et al (2003) noted that regular physical activity does not stimulate changes in diastolic function of the left ventricle in healthy aging men. Observation of Gates et al coincident with the result obtained in our control group, in which after the observation period was a significant reduction in boththe LVEDD and the LVEDV (p<0,001) [19]. Belardinelli et al (2001) did not notice significant changes in the left ventricle diastolic function in physically active patients compared with inactive, in the course of the 6-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…It is not resolved whether exercise training used in cardiac rehabilitation can improve diastolic function of the left ventricle [18]. Gates et al (2003) noted that regular physical activity does not stimulate changes in diastolic function of the left ventricle in healthy aging men. Observation of Gates et al coincident with the result obtained in our control group, in which after the observation period was a significant reduction in boththe LVEDD and the LVEDV (p<0,001) [19].…”
Section: Discussionmentioning
confidence: 99%